1997
DOI: 10.1002/chem.19970031010
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of the Metal—Silicon Bond in [M(SiR3)H3(PPh3)3] (M = Ru, Os) And the Crystal Structure of [Os{Si(N‐pyrrolyl)3}H3(PPh3)3]

Abstract: (1: M = Ru, R = Itortion along the 0s-Si axis from an idealised tetrahedral geometry for the central OsSiP, heavy-atom skeleton. The structure can be described as two face-shared octahedra, one based on osmium (OsH,P,) Keywords ab initio calculations hydrides osmium * ruthenium silicon and the other based on silicon (SiH,N,). Studies of the bonding situation in 2a reveal that the N-pyrrolyl substituents have a marked shortening cffect on the osmium-silicon distance (229.3 (3) pm) and that each of the three hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 38 publications
5
42
0
4
Order By: Relevance
“…Hübler et al proposed a bonding scheme that allows a facile rotation when considering the contribution represented in Figure 7 (b) to be preponderant. [23] On the contrary, Nikonov pleads an electron-density transfer from the σ(M-H) bonding orbitals into the σ‫(ء‬Si-N) antibonding orbitals to be the main contribution, thus leading to a rigid structure ( Figure 6 and Figure 7, a). [26] However, Nikonov uses a DFT study reported by Hübler et al to support his argumentation, but this was actually a MP2 study of an osmium analogue, which is certainly not transposable to the ruthenium case.…”
Section: Primary Silanesmentioning
confidence: 95%
“…Hübler et al proposed a bonding scheme that allows a facile rotation when considering the contribution represented in Figure 7 (b) to be preponderant. [23] On the contrary, Nikonov pleads an electron-density transfer from the σ(M-H) bonding orbitals into the σ‫(ء‬Si-N) antibonding orbitals to be the main contribution, thus leading to a rigid structure ( Figure 6 and Figure 7, a). [26] However, Nikonov uses a DFT study reported by Hübler et al to support his argumentation, but this was actually a MP2 study of an osmium analogue, which is certainly not transposable to the ruthenium case.…”
Section: Primary Silanesmentioning
confidence: 95%
“…6 The key to the low-energy barriers for the two reactions is the ability of Si to stabilize pentacoordination with an overall negative charge. Such a bonding situation has been found in the solid-state structures of several systems, [47][48][49][50][51][52][53][54][55][56] which suggests that it can also correspond to a low transition state in the appropriate case. The stabilization of the transition state is more important when the hypervalent Si species is more stable.…”
Section: Discussionmentioning
confidence: 92%
“…This effect is also evident from the theoretical calculations. 16 In the crystal structure of 22 the hydrides are located and the measured Os-H distances are 1.52(3), 1.66(3), and 1.57(3) Å. The calculated distances between silicon and hydrogen are Si‚‚‚H(1) ) 2.06(4) Å, Si‚‚ ‚H(2) ) 2.00(4) Å, and Si‚‚‚H (3) …”
Section: Synthesis Of Six-and Seven-coordinate Silyl Complexes Vmentioning
confidence: 97%